Investigation of Glucocorticoid Receptor Gene Bcl-1 Polymorphism in Rheumatoid Arthritis - Ali AYDENİZ,; Tuğçe SEVER,; Sacide PEHLİVAN,; Mustafa PEHLİVAN,; Özlem ALTINDAĞ,; Selin BÜDEYRİ,; Savaş GÜRSOY1, (Archives of Rheumatology, 2011)
Objectives: In this study, we investigated the association of the human glucocorticoid receptor gene (NR3C1) Bcl-1 CG polymorphism with clinical data and response to therapy among rheumatoid arthritis (RA) patients and healthy control subjects. Patients and methods: We performed PCR-RFLP (Polymerase chain reaction-restriction fragment length polymorphism) method for identifying restriction of the Bcl-1 fragment length polymorphisms in the intron 2 region of the NR3C1 gene in 65 patients with RA (47 females, 18 males) and 70 healthy control subjects (47 females, 23 males). Clinical parameters and demographic characteristics of the patients along with previous history of drug treatments were also recorded. In addition, patients' response to treatment was monitored with the visual analog scale (VAS), Disease Activity Scores 28 (DAS28) and Health Assessment Questionnaire (HAQ) scores. Results: The genotype frequencies of the NR3C1 Bcl-1 polymorphism did not differ between the patients with RA and the controls. We detected a deviation from the Hardy- Weinberg equilibrium in the RA group for the alleles tested (Rap=0.044, Kp=0.554). However, there was no significant difference between genotypes regarding age, gender, disease duration, or clinical parameters such as DAS28 scores, VAS and HAQ values (p>0.05). Conclusion: Although the glucocorticoid receptor gene Bcl-1 polymorphism did not differ between the RA and control groups, we detected a deviation from the Hardy-Weinberg equilibrium in the RA group for the alleles tested. This indicates that the glucocorticoid receptor polymorphism, namely Bcl-1CG, may play a role in the ethiopathogenesis of RA and the treatment response with glucocorticoids.